Tunisia : Report on the Observance of Standards and Codes; Data Module; Response by the Authorities; and Detailed Assessments Using the Data Quality Assessment Framework. (IMF Staff Country Reports; Country Report ;, 2006)
The methodological soundness of statistics in Tunisia is consistent in several areas with outdated international statistical standards. The Central Bank of Tunisia (BCT) is responsible for the collection, processing, and dissemination of monetary and balance of payments statistics. The accuracy and reliability of statistics in Tunisia are broadly adequate. Adequate national accounts data and some brief methodological notes are disseminated, albeit with no analyses accompanying the data. However, there is now a need to proceed quickly with the migration to the new standards.